Rationalization and Bureaucratization in the Indonesian Education System: An Analysis of Teacher Administrative Burden and Digitalization Complaints on KOMPAS Online Media - Inayah Islamiya, Nurul; Saputra, Hadi; Annisa, Nurul; Zalsabila, Naila (Indonesian Journal of Teaching and Learning, 2026)
Purpose – This study examines the phenomena of rationalization and bureaucratization in the Indonesian education system, focusing on teachers’ administrative burdens and complaints related to educational digitalization. The study is grounded in the growing implementation of efficiency-oriented, technology-driven education policies that aim to simplify bureaucracy but are often perceived by teachers as increasing administrative burdens. Methodology – A qualitative research design with a document analysis approach was employed. Data were collected from online media reports published by KOMPAS and Kompas.id using purposive sampling to select articles addressing teachers’ administrative workloads, bureaucratic simplification, digital education applications, and policy responses. Data were analyzed using thematic content analysis, including data reduction, categorization, and thematic interpretation, guided by Max Weber’s concept of the iron cage of bureaucracy. Findings – Policies emphasizing efficiency, accountability, and administrative modernization paradoxically expanded teachers’ administrative workloads. Digitalization has generated new forms of bureaucracy that demand continuous adaptation, increase work pressure, and shift teachers’ focus from pedagogical practices to documentation and reporting tasks. Consequently, teachers’ professional autonomy is diminished, revealing a misalignment between policy objectives and teachers’ lived experiences. Novelty – This study contributes original insights by combining media discourse analysis with Weberian bureaucratic theory to reveal the unintended consequences of digitalization on teacher professionalism and identity. Significance – The study has significant implications for policymakers, school administrators, and education researchers by highlighting the need to reorient policy to prioritize pedagogical quality and teacher autonomy.